Optimizing the Role of Schools and Communities in Protecting Children from Dropping Out through Community Service Programs - Muhammad Konginta Lubis; Melky Suhery Simamora; Leni Indrayani; Aripin Rambe (Outline Journal of Community Development, 2024)
Education is a basic right of children that must be protected from being hampered by socio-economic factors. One of the main challenges in the education sector is the high dropout rate, especially among children from underprivileged families. This study aims to explore and optimize the role of schools and communities in protecting children from dropping out of school through community service programs. This program involves collaboration between schools, communities, and the government to reduce factors that cause dropouts, such as economic problems, lack of motivation, and parental involvement. The results of the study showed that providing scholarships, additional learning facilities, and developing learning communities significantly supported the sustainability of children's education. However, challenges such as limited funds and difficulties in reaching remote areas still need to be addressed. Recommendations for program development include increasing accessibility, parental involvement, and partnerships with donor agencies. This program is expected to provide a sustainable positive impact on children's education in areas with high dropout rates.